Pembelajaran Bahasa Indonesia sebagai Linguistic Entrepreneurship: Implikasi terhadap Digital Marketing - Winata, Nana Triana; Damaianti, Vismaia S.; Syihabuddin, Syihabuddin; Mulyati, Yeti (Fakultas Seni Rupa dan Desain ITB, 2024)
Research on linguistic entrepreneurship in Indonesia is the newest one. This study analyzes the spoken and written language used in the coffee shop industry. This study aims to identify the language learning motivations of coffee shop business actors in marketing their products, specifically through the use of Indonesian in social media marketing and direct consumer outreach. This research employed descriptive qualitative methods to investigate the effects of linguistic entrepreneurship on coffee shop business actors, as well as to address variables that remain unclear and require further exploration. This research focuses on the resources available for using Indonesian both verbally and in writing. Business actors can seek linguistic entrepreneurship through their motivation to learn the language and the methods they employ to do so. The implication of using Indonesian in the economy is that it can serve as a policy for business. The research uniquely focuses on the Indonesian coffee shop industry as a specific context where linguistic entrepreneurship plays a vital role. The study delves into the connection between Indonesian language learning and entrepreneurial activities, particularly in thepromotion and marketing of coffee products.